The Friend and Colleague: “Fast Eddy” - Travis, Lawrence F. (Victims & offenders, 2021)
Edward Latessa and I joined the faculty of the University of Cincinnati together in 1980. Relying on memory, the paper traces the development of our friendship and describes the evolution of our relationship over time. The personal friendship is described first, followed by a description of the collegial relationship as peers and Latessa’s collegial behavior as an academic administrator. Recognizing the subjective nature of the material, an attempt is made to draw conclusions about Edward Latessa as both a personal friend and a professional colleague.